Substernal Goiter: a case to remember - Macedo,Sara Simões (2020)
SUMMARY Goiter is a localized or generalized thyroid hypertrophy. It can remain within the cervical region or grow down until it invades the mediastinum. The signs and symptoms depend on the size and location of the goiter. Although drugs and radioactive iodine are often used to treat thyroid disease, the presence of symptomatic substernal goiter is a clear indication for surgery. Death or postoperative complications rarely occur. We present a case of a 71-year-old man with recurrent thyroid pathology in the form of substernal goiter and hyperthyroidism even after partial thyroidectomy. The importance of this relates to the clinical evolution, volume, and location of the goiter as well as the surgical and pharmacological approach.